2022
DOI: 10.1136/bmjopen-2022-064050
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gaps in global evidence for nurse staffing and patient care outcomes research in low/middle-income countries: an umbrella review

Abstract: ObjectiveTo identify nurse staffing and patient care outcome literature in published systematic reviews and map out the evidence gaps for low/middle-income countries (LMICs).MethodsWe included quantitative systematic reviews on nurse staffing levels and patient care outcomes in regular ward settings published in English. We excluded qualitative reviews or reviews on nursing skill mix. We searched the Cochrane Register of Systematic Reviews, the Joanna Briggs Institute Database of Systematic Reviews and Impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Pediatric wards in low-resource settings are often overcrowded and understaffed, and a high nursing workload has been associated with medication errors and healthcare-associated infections. 35 , 48 – 51 Furthermore, staff misconceptions may hamper rational antibiotic use, as was illustrated here by the prescribers’ preference for cefotaxime over ceftriaxone, which lead to the hidden consequence of missed doses. Finally, also caretaker’s misconceptions have an impact, for example, oral switch is hampered by a high demand for “strong,” or intravenous medication.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric wards in low-resource settings are often overcrowded and understaffed, and a high nursing workload has been associated with medication errors and healthcare-associated infections. 35 , 48 – 51 Furthermore, staff misconceptions may hamper rational antibiotic use, as was illustrated here by the prescribers’ preference for cefotaxime over ceftriaxone, which lead to the hidden consequence of missed doses. Finally, also caretaker’s misconceptions have an impact, for example, oral switch is hampered by a high demand for “strong,” or intravenous medication.…”
Section: Discussionmentioning
confidence: 99%
“…First, this continuing practice will potentially deepen the maldistribution of nurses across the world; HICs have around 12 nurses per 1000 patients, and LMICs have 1 nurse per 2000 patients [ 10 ]. Around 90% of the global deficit of nurses is in LMICs [ 11 ]. Second, the true nursing shortage disproportionately affects South-East Asia, Eastern Mediterranean regions and Africa, and HICs are mostly recruiting from these regions [ 12 ].…”
Section: Worsening Equity In Healthcarementioning
confidence: 99%
“…Unlike traditional outcome-based quality indicators like mortality or length of stay, missed nursing care is a sole process-based indicator of patient care quality that is more likely to forewarn of worsening in nursing quality. 2 , 3 It is widespread and directly related to adverse outcomes. 4 Studies have showed that missed nursing care not only leads to negative patient outcomes such as less/poor quality of patient care (eg, bed sores, falls, and hospital-acquired infection) and lower patient satisfaction, but also result in increased ineffective pain management, malnourishment, and high mortality.…”
Section: Introductionmentioning
confidence: 99%